A case of acute disseminated encephalomyelitis following Mycoplasma pneumoniae infection. (2018) - Laila, Alla; El-Lababidi, Rania M.; Hisham, Mohamed; Mooty, Mohammad
Abstract: We report a case of acute disseminated encephalomyelitis (ADEM) secondary to Mycoplasma pneumoniae infection that failed to improve with methylprednisolone and intravenous immunoglobulin (IVIG); who responded with plasmapheresis. A 21- year- old female with an unremarkable medical history, initially presented to an outside hospital with fever and an influenza-like illness and was subsequently intubated for worsening sensorium. Brain magnetic resonance imaging was suggestive of ADEM or vasculitis for which she received five days of pulse steroids and IVIG. She showed no signs of improvement and was transferred to our hospital for plasmapheresis. Her work up revealed an elevated IgM antibody and positive sputum for Mycoplasma pneumonia by polymerase chain reaction, suggesting the pathogen as the culprit for her ADEM. Intravenous azithromycin and daily plasmapheresis were initiated for seven consecutive days. Following commencement of her treatment, the patient experienced good recovery and was subsequently extubated. She continued to improve with physical therapy and gained mobility, with the help of a walker. Patients commonly present with ADEM following viral infection or vaccination and less frequently post bacterial infection. The current treatment of ADEM due to Mycoplasma pneumoniae is based on limited case reports. Our patient poorly responded to pulse steroids and IVIG, while she markedly improved on azithromycin and plasmapheresis. In patients presenting with encephalopathic signs and neurological manifestations following pneumonia; Mycoplasma pneumoniae infection and subsequent immune-mediated demyelination should be considered.